Continued capacity: Factors of importance for organizations to support continued Let's Talk practice – a mixed‐methods study. (28th June 2020) - Allchin, Becca; Weimand, Bente M.; O'Hanlon, Brendan; Goodyear, Melinda
Abstract: Sustainability is a desired outcome of implementation. Understanding how organizations support new practices after implementation is important for sustainability. Let's Talk about Children (hereby referred to as 'Let's Talk'), a family‐focused intervention with parents with a mental illness, improves family, parent, and child outcomes. Little is understood about how organizations support sustained practice. The study aimed to (i) understand the implementation process that occurred in eight adult mental health services during a previous randomized controlled trial; (ii) establish their continued capacity to embed Let's Talk; and (iii) explore links between organizational capacity and sustained delivery by practitioners. This mixed method study used a questionnaire and individual interviews to collect data on the implementation process and current organizational capacity to support Let's Talk 12months after the randomized controlled trial. Links between organizational capacity and the adult mental health services with practitioners' continuing to use Let's Talk in the past 12 months were explored. Services with higher current organizational capacity scores had practitioners currently delivering Let's Talk. These services had all made changes to their organizational structures to support Let's Talk practice. All services experienced significant changes during and after implementation, influencing sustainability of Let's Talk. Addressing organizational capacity appears to be important to enable sustainability of Let's Talk implementation endeavours. Real‐world settings are constantly changing systems requiring ongoing tracking and adjustments to understand and support sustainability. Internal service development staff appear to support the shaping of organizational capacity to support Let's Talk; however, broader organizational support is needed for change within a complex system.